Regional and Rural-Urban Differences in the Use of Direct-acting Antiviral Agents for Hepatitis C Virus: The Veteran Birth Cohort. Issue 4 (April 2019) - Njei, Basile; Esserman, Denise; Krishnan, Supriya; Ohl, Michael; Tate, Janet P.; Hauser, Ronald G.; Taddei, Tamar; Lim, Joseph; Justice, Amy C.
Abstract : Background: Veterans with hepatitis C virus (HCV) infection may face geographic obstacles to obtaining treatment. Objective: We studied the influence of region and rural versus urban residence on receipt of direct-acting antiretroviral (DAA) medications for HCV. Subjects: Veterans receiving care within Veterans Affairs Healthcare System born between 1945 and 1965. Research Design: This is a observational study using national electronic health record data. Measures: Receipt of DAAs was defined as ≥1 filled prescription from January 1, 2014 to December 31, 2016. Region (South, Northeast, Midwest, and West) and residence (urban, rural-micropolitan, small rural towns, and isolated rural towns) variables were created using residential zone improvement plan codes and rural-urban commuting area (RUCA) codes. Multivariable models were adjusted for age, race, sex, severity of liver disease, comorbidities, and prior treatment experience. Results: Among 166, 353 eligible patients 64, 854 received, DAAs. Variation by rural-urban residence depended on region. In unadjusted analyses, receipt varied by rural-urban designations within Midwest, and West regions ( P <0.05) but did not vary within the South ( P =0.12). Southern rural small town had the lowest incidence of DAA receipt (40.1%), whereas the incidence was 52.9% in Midwestern isolated rural towns. In adjusted logistic analyses, compared with southern urban residents (the largest single group), southern rural small town residents had the lowest odds ratio, 0.85 (95% confidence interval, 0.75–0.93), and Midwestern residents from isolated and small rural towns had the highest odds (odds ratio, both 1.27) to receive treatment. Conclusions: Substantial geographic variation exists in receipt of curative HCV treatment. Efforts are needed to provide more equitable access to DAAs. Abstract : Supplemental Digital Content is available in the text.